Targeted DNA sequencing and in situ mutation analysis using mobile phone microscopy - Malte Kühnemund (Nature Portfolio, 2017)
On-site diagnostics technologies allow for rapid, cost-effective diagnosis with a particular importance for remote communities. Here the authors demonstrate the use of mobile phone based microscopy for targeted DNA sequencing andin situpoint mutation detection in tumours.